Development and initial qualitative evaluation of a novel school-based nutrition intervention - COOKKIT (Cooking Kit for Kids) - Simon Pini; William Goodman; Elizabeth Raby; Chris McGinley; Aurora Perez-Cornago; Fiona Johnson; Rebecca J. Beeken (BMC, 2023)
Abstract Background Excess weight and an unhealthy diet are risk factors for many cancers, and in high income countries, both are more prevalent among low income families. Dietary interventions targeting primary-school aged children (under 11) can improve healthy eating behaviours, but most are not designed to support the translation of skills learnt in the classroom to the home setting. This paper assessed attitudes and approaches to cooking and eating at home, and the potential to enhance engagement in healthy eating through the COOKKIT intervention. Methods COOKKIT is an intervention to deliver weekly cooking classes and supportive materials for low-income families to maintain healthy eating at home. Preliminary qualitative interviews were conducted with teachers and parent-child dyads from a range of primary schools in the UK to explore attitudes, barriers and facilitators for healthy eating and inform the development of COOKKIT. Following implementation, ten children (8-9 y/o) participated in post-intervention focus groups, alongside interviews with teaching staff and parents. Results Thematic analysis identified five themes under which to discuss the children's experience of food, cooking and the impact of COOKKIT: Involving children in planning and buying food for the family; Engaging children in preparing meals at home; Trying to eat healthy meals together in the midst of busy lives; Role-modelling; and Balancing practicalities, information and engagement when delivering cooking classes. Conclusions Results suggest COOKKIT provides engaging and easy to follow in-school resources for children and school staff with take-home kits facilitating continued engagement and reinforcing lessons learned in the home environment. Importantly, participants highlighted the combination of healthy eating information, applied practical skills and low costs could support families to continue following the COOKKIT advice beyond the intervention, suggesting further evaluation of COOKKIT is warranted.